Combined Analysis of SRAP and SSR Markers Reveals Genetic Diversity and Phylogenetic Relationships in Raspberry (Rubus idaeus L.) - Zhifeng Guo; Zhenzhu Fan; Xueyi Li; Haoqi Du; Zhuolong Wu; Tiemei Li; Guohui Yang (Agronomy)
Raspberry (Rubus idaeus L.) is a high-value horticultural crop recognized for its significant economic importance and exceptional nutritional profile. We analyzed 76 raspberry accessions (wild and cultivar) using simple sequence repeat (SSR) and sequence-related amplified polymorphism (SRAP) markers, and we established a standardized SRAP system for this species. Genetic similarity differed markedly between markers: SSR values spanned 0.47–0.98 (mean = 0.73), compared to the narrower range of 0.52–0.97 (mean = 0.75) for SRAP. Cultivar accessions exhibited higher intra-group homogeneity than wild accessions, and northeastern wild accessions showed more stable similarity metrics than Guizhou wild accessions. In hierarchical clustering, the resolution varied depending on the labeling marker. The cluster analysis by SSR markers identified two main clusters and further partitioned them into three clusters. In contrast, the SRAP system revealed two primary clusters, which subsequently diverged into five subclusters. SSR markers effectively captured population-level differentiation, whereas SRAP markers enabled precise discrimination of cultivars and ecotypes through non-coding region polymorphisms. Phylogenetic analyses confirmed closer genetic affinity between northeastern wild and cultivated accessions, which diverged significantly from Guizhou. This dual-marker approach revealed complementary information: SSR markers were used to survey genome-wide diversity, while SRAP markers were used to detect structural variations. Their integrated application enhances germplasm characterization efficiency and provides practical strategies for raspberry conservation and molecular breeding.